Gold Coated VO2 Nanogratings Based Plasmonic Switches - Bhardwaj, Priyanka; Roy, Manidipa; Singh, Sanjay Kumar (Trends in Sciences, 2022)
This paper presents 2 dimensional (2D) and 1 dimensional (1D) gold (Au) coated VO2 (Vanadium Dioxide) nanogratings based tunable plasmonic switch. VO2 is a phase changing material and hence exhibits phase transition from semiconductor to metallic phase approximately at 67 ºC or 340 K (critical temperature) which can be achieved by exposure to IR radiation, application of voltage, heating, etc. and there is a huge contrast between optical properties of its metallic and insulating phases and hence that can be utilized to implement VO2 based optical switches. These VO2 based gratings couple the incident optical radiation to plasmonic waveguide modes which in turn leads to high electromagnetic field enhancement in the gaps between the nanogratings. The proposed Au coated VO2 nanogratings can be fabricated by using current state of art fabrication techniques and provides switchability of the order of femtoseconds. Hence the optical switching explained in our paper can be used fast switching applications. For an optimum switch our aim is to maximize its differential reflectance spectra between the 2 states of VO2, i.e., metallic and semiconductor phases. Rigorous Coupled Wave Analysis (RCWA) reveals that wavelengths for maximum differential reflectance can be optimized over a large spectral regime by varying various parameters of nanogratings for example groove height (h), width (w), gap (g) between the gratings, and thickness (t) of Au coating over VO2 by simulation using RCWA for maximum differential reflectance between VO2 metal and semiconductor phase, i.e., the switching wavelengths can be tuned by varying grating parameters and thus we can have optimum optical switch.